Sol LeWitt. The Conceptuality of Drawing - Paolo Belardi (Diségno)
Two significant faxes can be found in the archive of the ‘Pietro Vannucci’ Academy of Fine Arts in Perugia: they are worthy of note both because they are signed by two well-known personalities (Sol LeWitt and Bruno Corà) and because they markedly represent a genuine manifesto which is theoretically capable of healing the fracture that traditionally separates architecture and art history in matters of drawing intended as a form of thought. In the first fax, dated March 22, 1995, LeWitt (at the time residing for long periods in Spoleto) tells his friend Bruno Corà (then professor of Art History in the Academy) about the delivery of the maquette of a work created specifically for Perugia [1]: an ‘open cube’ (the solid form most loved by LeWitt [2]) which, as an element of the exhibition project City and Art, aimed at injecting viral works into extra moenia urban areas of symbolic interest, was to be exhibited in the portico of the large public building built in those same years by Aldo Rossi and located on the western side of the Piazza Nuova in Fontivegge [3].